Mid-infrared, spatially resolved spectroscopy of the nucleus of the Circinus galaxy - Roche, P; Packham, C; Telesco, C; Radomski, J; Alonso-Hererro, A; Aitken, D; Colina, L; Perlman, E (2006)
High spatial resolution spectroscopy at 8-13 μm with T-ReCS on Gemini-S has revealed striking variations in the mid-infrared emission and absorption in the nucleus of the Circinus galaxy (hereafter Circinus) on subarcsecond scales. The core of Circinus is compact and obscured by a substantial column of cool silicate dust. Weak extended emission to the east and west coincides with the coronal line region and arises from featureless dust grains which are probably heated by line emission in the coronal emission zone. The extended emission on the east side of the nucleus displays a much deeper silicate absorption than that on the west, indicating significant columns of cool material along the line of sight and corresponding to an additional extinction of A V ∼ 25 mag. Emission bands from aromatic hydrocarbons are not subject to this additional extinction, are relatively weak in the core and in the coronal line region, and are much more spatially extended than the continuum dust emission; they presumably arise in the circumnuclear star-forming regions. These data are interpreted in terms of an inclined disc-like structure around the nucleus extending over tens of parsecs and possibly related to the inner disc found from observations of water masers by Greenhill et al. © 2006 RAS.